Various modalities of treatment in distal radius fracture - B.S.Brar; Jagdip Rhency; Harish Khichy; Rohit Sharma (GMC Patiala Journal of Research and Medical Education, 2019)
Fractures of the distal end of the radius are common injuries and are the commonest bony injury around the wrist. Management of distal radius fractures has changed significantly since Colle's proclamation in 1814. Our study is intended to find out both conceptual and practical guidance for precision treatment with an expectant favorable result. This prospective and observational study was conducted on patients with distal end radius fractures treated with closed reduction and cast immobilisation with or without percutaneous pinning, external fixation and volar plating. Methods: 60 patients of distal end radius fractures were treated with Cast immobilization, Percutaneous Pinning and plaster immobilization, External fixation and Volar locking plate fixation. AO classification was used. Functional outcomes were assessed using “Demerit point rating system” of Gartland & Werley (modified). Patients were followed for an average of 6 months. Results: Patients ranged from 18-60 years of age. Average age was 39.35±12.15years. Female:Male sex ratio was1.6:1. Fall on outstretched hand was the leading causes of injury in 38(63.3%) patients and road side accidents was the second major cause in 20(33.3%) patients. Right side in 44 (73.3%) patients and dominant hand in 42 (70%) patients was most commonly involved in present study. Maximum number of patients had A2 fracture 14(23.3%). Patients were treated according to AO classification. The most common complication encountered among the patients was stiffness. Final subjective evaluation was done using Modified Gartland and Werley Scoring System . We observed excellent to good results in 10(83.3%) patients and fair results in 1 2(16.7%) patients treated with cast immobilisation group. Excellent to good results in 6(75%) patients and fair results in 2(25%) patients treated with percutaneous pinning with cast immobilisation. Excellent to good results in 13(65%) patients and fair results in 7(35%) patients treated with external Fixation. Excellent to good results observed in 18(90%) patients in and fair results in 2(10%) patients treated with volar plating. Conclusions: Volar locking plating is a safe and effective treatment for unstable fractures. Specially locking implants provide advantages in fractures with metaphyseal comminuted zones.